Koherensi Kebijakan Food Estate dengan Kebijakan Ketahanan Pangan dan Gizi - Chairunisa S. Hakim (Yayasan Pendidikan Medika Indonesia, 2022)
The objective of this study is to determine how the actor, context and policy process in coherence of Food Estate policy with the Food Security and Nutrition Policy. This study adopted a qualitative single case study design drawing on in-depth interviews, policy document review and literature study. Content Analysis and Transcendental Phenomenological Analysis were used in this study. The theories used as analytical tools in this research are 1) Policy Coherence theory developed by Nilsson, 2) Policy Triangle theory developed by Walt and Gilson, and 3) Advocacy Coalition Framework theory by Sabatier & Jenkins as a triangulation method. The results show that the coherence of the Food Estate Policy with the Food Security Policy is acceptable but not being at its optimum, because there is no objective written that represent Skor Pola Pangan Harapan or Pedoman Gizi Seimbang. The interactions between actors, context, and policy-making process are closely related and influence policy coherence. Using the Advocacy Coalition Framework as a triangulation method, it is known that both civil society organizations and the government want to achieve food and nutrition security, but civil society organizations have different approaches regarding how to achieve food and nutrition security.